The Kentucky Fried Chicken Integrated Marketing Communications Mix Strategy and Its Sales Revenue, Profitability, and Market Share - Guinto, Arman L.; Alcantara, Antonio N. (Future Science / FSH-PH Publications, 2022)
The main objective of the study was to assess the level of effectiveness of KFC integrated marketing communications (IMC) mix strategy and its correlation to the marketing outcomes. The study specifically aimed to answer the following: (1) Profile of the respondents – customers and managers; (2) Assessment of the respondents on the effectiveness of IMC mix strategy of KFC in terms of the following aspects: Personal Selling, Non-Personal Selling, Direct Selling, Sales Promotion, Advertising, and Public Relations; (3) To answer whether there is a difference on the assessment of customers and managers on the effectiveness of IMC mix strategy; (4) To answer whether there is a difference on the assessment of customers and managers on the effectiveness of KFC IMC mix strategy when they are grouped by common profile; (5) To answer whether there is a difference on the assessment of customers on the effectiveness of KFC IMC mix strategy when they are grouped by profile; and (6) To answer whether there is a relationship between KFC IMC mix strategy and marketing outcomes. The design of this study is descriptive research which is aiming to record, describe, analyze, interpret and compare the facts, data and information gathered through survey about the IMC mix strategy of selected KFC stores in Metro Manila, questionnaires were distributed to the respondents. A total of five hundred fifteen (515) respondents had chosen using convenience sampling, consisting of customers and managers. Results showed the respondents’ assessment on the effectiveness of IMC mix strategy of KFC, the most effective among the elements is public relations while the least is sales promotion, over-all the IMC mix strategy of KFC is effective.